Application of Different Insecticides by Drip Irrigation Method Against European Corn Borer on Corn Crops - Melnichuk, Fedir; Alekseeva, Svitlana; Hordiienko, Oleksandra; Retman, Mykhailo (Polish Journal of Natural Sciences, 2023)
The peculiarities of the development and dynamics of the population density of European corn borer on corn crops under irrigation were studied in 2019-2021 in conditions of Steppe of Ukraine. Field investigations were conducted according to generally accepted methods. The size of the experimental plots in the field experiments was 50 m2 (10.4x4.8 m), the replication was 4 times. Allocation of plots was randomized. The beginning of the first adults flight was observed in the 1st decade – in the middle of June at average. Mass laying of eggs and the flight of more than 50% of the butterfly population occurred in the 3rd decade of June, which coincided with the phase of pollen shedding of corn plants. Mass flight of the butterfly (flight of more than 75% of the population) was observed at the end of the 3rd decade of June – the beginning of the 1st decade of July. The revival of caterpillars began in the third decade of June and continued until the end of July. The average population density of European corn borer caterpillars in 2019-2021 were 1.6 and 1.8 specimens per stem on corn crops. Larvae damaged up to 34.5-37.8% of the plants stems of this crop. Results of field studies of the insecticides (from the group of neonicotinoids and anthranilic diamides) effectiveness applied together with irrigation water against this pest are given.